Denote a manifold by $M$, and the tangent bundle on this by $\tau_M$, the normal bundle by $\nu_M$.

We can consider the whitney sum of these bundles denoted here: $\tau_M\oplus \nu_M$.

This should be obtained as: $$\begin{matrix}E_1\oplus E_2&\longrightarrow&E_1\times E_2\\\downarrow&&\downarrow\\B&\stackrel{d}{\longrightarrow}&B\times B\end{matrix}$$

Such that the projection for $\tau_M\times\nu_M$ is given by $$\pi_1\times \pi_2:E_1\times E_2\to B\times B$$ gives us the induced projection from $E_1\oplus E_2$ i.e. $\pi_3:E_1\oplus E_2\to B$ where $$E_1\oplus E_2= \{(b,(e_1,e_2)):d(b)=(b,b)=(\pi_1(e_1),\pi_2(e_2))\}$$ and thus $$\pi_3:(b,(e_1,e_2))\mapsto b.$$

Does this give us that $\pi_3^{-1}(b)=\{b\}\times\pi_1^{-1}(b)\times \pi_2^{-1}(b)$?


Yes, it does give you $\pi_3^{-1}(b) = \{b\} \times \pi_1^{-1}(b) \times \pi_2^{-1}(b)$. If you want you can do it by double inclusion:

  • Suppose that $\xi = (b, e_1, e_2) \in \pi_3^{-1}(b)$, then by definition $(\pi_1(e_1), \pi_2(e_2)) = d(b) = (b,b)$, i.e. $\pi_1(e_1) = \pi_2(e_2) = b$, in other words $e_1 \in \pi_1^{-1}(b)$ and $e_2 \in \pi_2^{-1}(b)$. It follows that $\xi \in \{b\} \times \pi_1^{-1}(b) \times \pi_2^{-1}(b)$.

  • Conversely suppose that $\xi = (b, e_1, e_2) \in \{b\} \times \pi_1^{-1}(b) \times \pi_2^{-1}(b)$. Then you do have $(\pi_1(e_1), \pi_2(e_2)) = (b,b) = d(b)$ and so $\xi \in E_1 \oplus E_2$, and of course $\pi_3(\xi) = b$.

In the future, you can note that it's easier to work with the following description of $E_1 \oplus E_2$: $$E_1 \oplus E_2 = \{ (e_1, e_2) \in E_1 \times E_2 \mid \pi_1(e_1) = \pi_2(e_2) \}$$ with the projection $\pi_3$ given by $\pi_3(e_1, e_2) = \pi_1(e_1) = \pi_2(e_2)$. Roughly speaking, $E_1 \oplus E_2$ is the bundle over $B$ with fibers the products of the fibers of $E_1$ and $E_2$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.